Diboron(4)‐Catalyzed Remote [3+2] Cycloaddition of Cyclopropanes via Dearomative/Rearomative Radical Transmission through Pyridine. (29th November 2022) - Xu, Ming; Wang, Zhijun; Sun, Zhaohui; Ouyang, Yizhao; Ding, Zhengwei; Yu, Tao; Xu, Liang; Li, Pengfei
Abstract: Ring structures such as pyridine, cyclopentane or their combinations are important motifs in bioactive molecules. In contrast to previous cycloaddition reactions that necessitated a directly bonded initiating functional group, this work demonstrated a novel through‐(hetero)arene radical transmission concept for selective activation of a remote bond. An efficient, metal‐free and atom‐economical [3+2] cycloaddition between 4‐pyridinyl cyclopropanes and alkenes or alkynes has been developed for modular synthesis of pyridine‐substituted cyclopentanes, cyclopentenes and bicyclo[2.1.1]hexanes that are difficult to access using known methods. This complexity‐building reaction was catalyzed by a very simple and inexpensive diboron(4) compound and took place via dearomative/rearomative processes. The substrate scope was broad and more than 100 new compounds were prepared in generally high yields. Mechanistic experiments and density function theory (DFT) investigation supported a radical relay catalytic cycle involving alkylidene dihydropyridine radical intermediates and boronyl radical transfer. Abstract : Previously challenging pyridinyl cyclopentanes, cyclopentenes and bicyclo[2.1.1]hexanes with multiple substituents now can be efficiently prepared via a remote [3+2] cycloaddition reaction. The reaction features a simple diboron(4) catalyst, modular disconnection mode, broad scope, high atom economy and a unique dearomative/rearomative mechanistic process.